Bound [videorecording (DVD)] - Woofter, Isaac Hirotsu; Karimloo, Ramin, 1978-; Pimentel, Jessica; Sadeghian, Alexandra Faye (Freestyle Digital Media, 2025)
To escape her drug-dealing stepfather, a young artist flees to NYC with only her pet pocket squirrel. After successfully reinventing herself with the help of some found family, she returns home to confront her dark past, in order to truly be free.